Elite sport return to training guidance: Stage One (Department for Digital, Culture, Media & Sport, 2020)
The coronavirus (COVID-19) pandemic has presented a significant challenge to this country. Everyone`s actions, including those of elite athletes and sporting bodies, have helped to reduce the transmission of coronavirus in our communities.